KIVA Program for Trauma Healing due to Cyber-bullying among Students - Aris Widiyanto; Joko Tri Atmojo; Rina Tri Handayani (Masters Program in Public Health, Sebelas Maret University, 2018)
Background: Cyber-bullying involves the use of electronic media with the aim of causing damage, humiliation, suffering, fear, and despair for individuals who are the targets of aggression. The impact of cyber-bullying is not only affect their daily lives but may continue to adulthood. KiVa is research-based anti-bullying program that has been developed in the University of Turku, Finland, with funding from the Ministry of Education and Culture. The effectiveness of KiVa has been shown in a large randomized controlled trial. This study aimed to describe the health problems and evidence-based intervention programs that support trauma healing through KiVa program.Subjects and Method: A systematic review was conducted by searching the following databases: PubMed, SAGE Journals and Virtual Health Library from 2010 until 2018. The keywords for this review included cyber-bullying AND children, cyber-bullying AND mental health AND Children, cyber-bullying in children AND intervention. The inclusion criteria were systematic review, clinical review, cohort study, cross-sectional study, clinical study and guidelines. After the review process, 19 articles and 1 RCT were included.Results: Internationally, the impact of cyber-bullying on children has been linked to poor mental health including overall psychological health, low self-esteem, depression and anxiety and violent behavior. Another study showed that bully victims had the highest risk of self-injury, suicidal ideation, suicide plan and effort. KiVa is a school-based anti-bullying program from Finland involving teachers, students and parents. The KiVa principle is the prevention of bullying by cultivating character in students by forming group norms. The forms vary, can be videos, online games, surveys, posters, and guidebooks for parents. Children are taught a sense of responsibility and empathy. Previous RCT studies which involved 2,042 students in grades 4 and 6 showed that KiVa reduced intimidation, pro-intimidation, and victimization. And increasing attitude and empathy for victims. Overall, the findings provide evidence of the effectiveness of the KiVa Program.Conclusion: Cyber-bullying is associated with emotional stress and even suicide attempts. Parents, health personnels, and educators must be aware of the long-term risks so that prevention and treatment programs such as KiVa should be considered to be applied in Indonesia.Keywords: Cyber-bullying, children, mental healthCorrespondence: Aris Widiyanto. School of Health Sciences Mamba'ul 'Ulum, Surakarta, Jl. Ring Road Utara, Tawangsari, Mojosongo, Jebres, Surakarta, Central Java. Email: widiyantoaris99@gmail.com. Mobile: +6281329209095Health Promotion and Behavior (2018), 3(4): 263-269https://doi.org/10.26911/thejhpb.2018.03.04.06